Utilisation of computer simulation for dynamic calculation of train delays - Fikejz, Jan; Brožek, Josef (EUROSIS-ETI, 2018)
This article deals about utilisation of computer simulation for dynamic calculation of train delays within the rail network model and satellite navigation. Attention is firstly aimed on the description of the trains position in the designed railway network model. Further attention is focused on the design of the dynamic calculation of train delays with utilization of reduced track profile and using computer simulation.
Využití počítačové simulace pro dynamický výpočet zpoždění vlaku
Keywords: Utilisation; computer; simulation; dynamic; calculation; train; delays; Využití; počítačové; simulace; dynamický; výpočet; zpoždění; vlaku